Medical certificate verification system using QR code - Lai, Chong Lan (2014)
A medical certificate verification system based on QR technology is described in this project. Based on the problem statement, medical certificate is university used to as a record that an employee unable to attend to an office. It is simply too easy to obtain a sick certificate and to stay off work on full pay. Forged medical certificate has been used by students to absent their class. However, due to lack of integrity among the citizens, people tend to purchase or create forged medical certificates from various website that offers these documents. The objectives of this project are to study the QR technology and document authentication process, and also develop a medical certificate verification system using QR code and to validate the functionality of the system. The QR technology method is applied in this project for performing an easy way to check the verification of a medical certificate. The method that have been used is for encode the information data to protect the data from being forge. Thus, the end user can verify the medical certificate using any device with QR reader application to decode the data and get the real information from it.